2020
DOI: 10.1002/brb3.1603
|View full text |Cite
|
Sign up to set email alerts
|

Electroantennogram reveals a strong correlation between the passion of honeybee and the properties of the volatile

Abstract: Insects depend on the detection of volatile compounds through their specialized olfactory sensilla for basic functions like foraging, preda

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…For olfactory communication, honeybees use their antennae to recognize and respond to specific odors. Recent studies have revealed the bees’ distinct electrophysiological responses to different chemicals with quantifiable preferences ( 9 ). Olfactory communication with pheromones is crucial for many coordinated processes inside a honeybee colony, such as caste recognition, regulating foraging activities, and alarm broadcasting ( 10 12 ).…”
mentioning
confidence: 99%
“…For olfactory communication, honeybees use their antennae to recognize and respond to specific odors. Recent studies have revealed the bees’ distinct electrophysiological responses to different chemicals with quantifiable preferences ( 9 ). Olfactory communication with pheromones is crucial for many coordinated processes inside a honeybee colony, such as caste recognition, regulating foraging activities, and alarm broadcasting ( 10 12 ).…”
mentioning
confidence: 99%
“…Holzer & Shimoyama (1997) groundbreakingly controlled a live cockroach to walk along a black line by stimulating its antenna with an electronic backpack. Similarly, since physical activities of antenna can affect the motion of insects, the electroantennography (EAG) of honeybees under different odors was investigated to analyze the response of samples in order to provide physical support to control live honeybees (Zhao et al, 2020). Furthermore, cyborgs with other functional modules, such as a kind of electrical stimulated cyborg mounted on a sound source localization module, came out (Latif et al, 2016 demonstrated the achievement of free-flight thrust control of cyborg beetles (Vo Doan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed the bees' distinct electrophysiological responses to different chemicals with quantifiable preferences [Zhao et al, 2020]. Olfactory communication with pheromones is crucial for many coordinated processes inside a honey bee colony, such as caste-recognition, regulating foraging activities, and alarm-broadcasting [Trhlin et al, 2011, Pankiw et al, 1998, Lensky and Cassier, 1995.…”
Section: Introductionmentioning
confidence: 99%